THE EXPERIENCE OF THE AUTOMATION OF THE STATISTICAL REPORTING FORMATION ON WAGES IN MULTIDISCIPLINARY MEDICAL INSTITUTION - O. E. Karpov; D. N. Nikitenko; O. Ya. Gembara; T. A. Manakova (Статистика и экономика, 2018)
The article is dedicated to the description of the experience of automation of the processes of statistical reporting on salaries in Federal State Budgetary Institution «NationalPirogovMedicalSurgicalCenter» of Ministry of Health of theRussian Federationwith the use of information systems.According to the current legislation of theRussian Federation, within the framework of the successful implementation of the «Road Map» on a national scale, statistical information about salaries of employees of social institutions is collected in various sections of data reporting. It became necessary to develop a tool to promptly collect, process and analyze data on salaries to provide statistical information to social institutions.The purpose of this article is to familiarize oneself with the concept of multidimensional data representation and to structure information on multidimensional analytical reports within the framework of practical application for solving economic problems related to the formation of statistical reporting on salaries. The algorithm and the procedure for the formation of multidimensional analytical reports are described, both from the methodological and from the practical point of view. As a material for this study, the normative and legal acts of the Russian Federation, statistical and analytical materials of the section «Salaries of certain categories of workers in the social sphere and science» of the Federal State Statistics Service of the Russian Federation, scientific publications and articles of the periodical press, as well as the results of their own research were used.To facilitate the perception, special attention is given to the description of the basic concepts of multidimensional analytical reporting: measure, performance variables, value. The authors not only gave a definition of multidimensional analytical reporting, but also demonstrated a visual representation of the multidimensional information space of performance variables.Based on these definitions, the article describes the system for developing multidimensional analytical reporting, examines the stages of designing a multidimensional analytical representation of data, and demonstrates how to set up a multidimensional analytical report for building a multi-level hierarchy in accordance with pre-selected performance variables and dimensions.Methods of working with multidimensional analytical reporting are also described on the example of the implementation of the formation of the multidimensional analytical report «Statistical reporting on salaries» in the information system of the Federal State Budgetary Institution «NationalPirogovMedicalSurgicalCenter» of Ministry of Health of theRussian Federation.As a result, the effectiveness of multidimensional analytical reports for collecting, monitoring and analyzing statistical information on salaries was proved. Conducting in-depth analysis and evaluating the results of the implementation of salary targets are the basis for further modeling of the pay system and forecasting of financial results. Thus, the introduction of multidimensional analytical reporting made it possible to facilitate the labor-intensive process of making strategic management decisions by the administration of the institution.The authors concluded that the availability of such a tool in the healthcare system could help accelerating the operational processing of information for data analysis, as well as the generation of reports in various sections with an established depth of detail.